1991
DOI: 10.1090/s0002-9947-1991-1005084-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Hölder and $L\sp p$ estimates for $\overline\partial\sb b$ on the boundaries of real ellipsoids in ${\bf C}\sp n$

Abstract: ABSTRACT. Let D be a real ellipsoid in en, n ~ 3, with defining function p(z) = E~=I (x~nk + y~mk) -1, zk = x k + iYk ,where n k , mk EN. In this paper we study the sharp HOlder and L P estimates for the solutions of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Proof of Theorem Let ϕ be a (0,1)‐form satisfying the compatibility condition, that is, bΩϕα=0 for every continuous up to the boundary ¯‐closed (2,0)‐form α on Ω. M.C. Shaw [30, 31] showed that u:=Tbϕ=H+ϕHϕis an integral solution (in the distribution sense) to the ¯b‐equation, ¯bu=ϕ, on bΩ where H+ϕfalse(zfalse):=14π2limε0+bΩHfalse(ζ,zεν(z)false)ϕfalse(ζfalse)ωfalse(ζfalse),Hϕfalse(zfalse):=14π2limε0+bΩHfalse(z+εν(z),ζfalse)ϕfalse(ζfalse)ωfalse(ζfalse).Here ν(z) is the outward unit normal vector at zbΩ; ωfalse(ζfalse)=dζ1dζ2; and H(ζ,z) is given by …”
Section: Proof Of Theorem 12 and Theorem 13mentioning
confidence: 99%
See 3 more Smart Citations
“…Proof of Theorem Let ϕ be a (0,1)‐form satisfying the compatibility condition, that is, bΩϕα=0 for every continuous up to the boundary ¯‐closed (2,0)‐form α on Ω. M.C. Shaw [30, 31] showed that u:=Tbϕ=H+ϕHϕis an integral solution (in the distribution sense) to the ¯b‐equation, ¯bu=ϕ, on bΩ where H+ϕfalse(zfalse):=14π2limε0+bΩHfalse(ζ,zεν(z)false)ϕfalse(ζfalse)ωfalse(ζfalse),Hϕfalse(zfalse):=14π2limε0+bΩHfalse(z+εν(z),ζfalse)ϕfalse(ζfalse)ωfalse(ζfalse).Here ν(z) is the outward unit normal vector at zbΩ; ωfalse(ζfalse)=dζ1dζ2; and H(ζ,z) is given by …”
Section: Proof Of Theorem 12 and Theorem 13mentioning
confidence: 99%
“…The purpose of this paper is to prove Lp estimates, 1p, for the tangential Cauchy–Riemann equation ¯bu=f on a class of convex, infinite‐type ellipsoids Ωdouble-struckC2. We construct an explicit solution to the ¯b‐equation using the Henkin solution for the Cauchy–Riemann equation and an idea of Shaw [30, 31]. We also present two applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further estimates for ff b are given in [2], [3], [14], [17], [18], [19]. Further estimates for ff b are given in [2], [3], [14], [17], [18], [19].…”
mentioning
confidence: 99%